Nonmydriatic Photographic Screening for Diabetic Retinopathy in Pregnant Patients with Pre-Existing Diabetes in a Safety Net Population: 1 Year Results from the Diabetic Retinopathy in Pregnant Patients Study - Malini Veerappan Pasricha; Jodi So; David Myung; Andrea Jelks; Carolyn K. Pan (Women's Health Reports, 2020)
Background: Pregnant patients with pre-existing diabetes mellitus (DM) are at increased risk for development or progression of existing diabetic retinopathy (DR). A quality improvement project was initiated to improve DR screening during pregnancy at a safety net hospital. This article highlights the utility and generalizability of our telemedicine-based screening model. Materials and Methods: In April 2018, we implemented a photographic retinal screening system in the Maternal Fetal Medicine (MFM) clinic at Santa Clara Valley Medical Center in San Jose, CA. The system is intended to screen all pregnant patients with pre-existing diabetes (type 1 and 2). Retinal images are automatically uploaded to a secure server and interpreted by a retina specialist (C.K.P.). Results: A total of 71 pregnant patients with pre-existing DM were seen in the MFM clinic during the study period. Sixty-six of 71 patients (93.0%) were screened compared with 69.1% in the year prior. Of the 64 patients screened with readable images 11 (17.2%) had DR, whereas 53 did not. Forty-nine of the 64 (74.2%) patients screened underwent screening using the new nonmydriatic system in the MFM clinic. Only 7 out of 47 (14.9%) patients with readable images in the MFM clinic required referral to the ophthalmology clinic. Conclusion: Our model for DR screening in pregnant patients in safety net hospitals is effective in improving screening rates and expediting evaluation and treatment for those in need. This system can prevent irreversible vision loss in pregnant patients and provides an effective framework for ophthalmic care in a safety net hospital system.